2016
DOI: 10.1017/s0022050716000590
|View full text |Cite
|
Sign up to set email alerts
|

Obama, Katrina, and the Persistence of Racial Inequality

Abstract: New benchmark estimates of Black-White income ratios for 1870, 1900, and 1940 are combined with standard post-World War census data. The resulting time series reveals that the pace of racial income convergence has generally been steady but slow, quickening only during the 1940s and the modern Civil Rights era. I explore the interpretation of the time series with a model of intergenerational transmission of inequality in which racial differences in causal factors that determine income are very large just after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 110 publications
(153 reference statements)
2
29
0
Order By: Relevance
“… Margo (, footnote 16), however, has noted that my 0.8 autoregressive coefficient for a accords well with his evidence on the intergenerational convergence between African‐American and White incomes in the US. …”
supporting
confidence: 64%
“… Margo (, footnote 16), however, has noted that my 0.8 autoregressive coefficient for a accords well with his evidence on the intergenerational convergence between African‐American and White incomes in the US. …”
supporting
confidence: 64%
“…In the absence of differences in intergenerational mobility by race, racial disparities in income would dissipate relatively rapidly across generations given observed levels of mobility and vanish entirely in steady-state. Hence, an intergenerational model with constant relative and absolute mobility is clearly inconsistent with the persistence of income disparities by race throughout America's history (Myrdal 1944;Duncan 1968;Margo 2016).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Differences in economic outcomes by race have persisted for centuries in the United States and continue up to the present day (Myrdal 1944;Duncan 1968;Margo 2016). For example, in 2016, the median household income of black Americans was $39,500, compared with $65,000 for non-Hispanic white Americans (U.S. Department of Commerce, Bureau of the Census 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity in intergenerational income elasticities is believed to exist for many reasons. For instance, researchers have concluded that intergenerational income elasticities are larger for blacks than whites (Duncan 1968, Margo 2016 and that patterns of mobility are substantially different for farmers compared to non-farmers (Hout andGuest 2013, Xie andKillewald 2013). If one group is over-represented in the linked data, this will bias inferences about the historical rate of the population's intergenerational mobility.…”
Section: A How Type I Errors Affect Inferencesmentioning
confidence: 99%